Automatic Sliding Gate System with IoT Capability - Budhi Anto; Dahliyusmanto; Eddy Hamdani (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Riau, 2025)
This paper presents a novel automatic sliding gate system with IoT capability enabling it to be controlled through the Internet using a smartphone. The system is built on three main parts: sliding gate opener (SGO) with its driving mechanism, electronic control unit (ECU), and an Android smartphone with application software to communicate with the ECU. The SGO is driven by a 12-pole permanent-split-capacitor (PSC) motor coupled with speed reducer gearbox and uses a rack-pinion power transmission. The ECU, which is based on two microcontroller modules working in a cascade arrangement, controls the movement of the PSC motor in either forward or reverse rotation according to the information gained from a set of mechanical switches, inductive proximity sensors, and commands from the smartphone. The first microcontroller module is an Arduino UNO, functions to control the operation of PSC motor. The second is an ESP32 NodeMCU rolling as a communication controller between the ECU and smartphone. The SGO can also be controlled locally at the gate site by using a set of mechanical switches mounted on the control panel of the sliding gate system. The sliding gate system employs two inductive proximity sensors installed at the ends of the SGO movement to give information to the Arduino to stop the motor automatically as the SGO approaches the sensor position. The functional test has been conducted on the sliding gate system and the results show that the SGO movement can be controlled locally through pushbutton switches and remotely using an Android smartphone.